2014
DOI: 10.1371/journal.pone.0107145
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Alters Intrinsic Functional Connectivity of the Right Posterior Insula: A Pharmacological Resting State fMRI Study

Abstract: BackgroundModafinil is employed for the treatment of narcolepsy and has also been, off-label, used to treat cognitive dysfunction in neuropsychiatric disorders. In a previous study, we have reported that single dose administration of modafinil in healthy young subjects enhances fluid reasoning and affects resting state activity in the Fronto Parietal Control (FPC) and Dorsal Attention (DAN) networks. No changes were found in the Salience Network (SN), a surprising result as the network is involved in the modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…Using related strategies with MUD populations (or particularly those with co-occurring depression, anxiety, or PTSD) may therefore be beneficial for interrupting the negative reinforcement cycle. Additionally, other pharmacological interventions may also be useful for altering dysfunctional brain regions in MUD, such as modafinil, which has been shown to increase insula and ACC RSFC with other brain regions (116). By exploring interventions that target dysfunctional brain regions highlighted in the literature on MUD, researchers may be able to develop treatments that break the negatively reinforcing cycle of using methamphetamine to reduce uncomfortable sensations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Using related strategies with MUD populations (or particularly those with co-occurring depression, anxiety, or PTSD) may therefore be beneficial for interrupting the negative reinforcement cycle. Additionally, other pharmacological interventions may also be useful for altering dysfunctional brain regions in MUD, such as modafinil, which has been shown to increase insula and ACC RSFC with other brain regions (116). By exploring interventions that target dysfunctional brain regions highlighted in the literature on MUD, researchers may be able to develop treatments that break the negatively reinforcing cycle of using methamphetamine to reduce uncomfortable sensations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…When Esposito and colleagues examined the activity of seven resting-state cortical networks, they found that in the absence of structural changes modafinil intake increases activity in the Dorsal Attention Networkthought to modulate externally-directed attention by amplifying or attenuating the saliency of relevant and irrelevant cues -and increased connectivity in the anterior cingulate cortex (ACC) node of the left Frontal Parietal Control network (Esposito et al, 2013) -which may mediate planning across domains (Spreng et al, 2010). On further analysis, this group found that although overall activity in the Saliency Network -which orients attention towards key environmental stimuli and helps guide behaviour -was unchanged, functional coupling between the right posterior insula, a key network node, and the rest of the network was strengthened (Cera et al, 2014).…”
Section: Imaging Studiesmentioning
confidence: 99%
“…On the other hand, mixed patterns of rsFC increase and reduction were found for methylphenidate encompassing motor and limbic (Farr et al, 2014, Kline et al, 2016, Mueller et al, 2014, as well as DMN, SN, and CEN nodes (Sripada et al, 2013). Moreover, the stimulant modafinil, which is like GHB clinically used for narcolepsy treatment, increased rsFC between the insula and the putamen, the superior frontal gyrus, and the ACC (Cera et al, 2014), and of the left CEN to the pre-supplementary motor area (preSMA), the occipital pole, and the inferior parietal gyrus (Esposito et al, 2013) in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%